Growth Profit In Islamic Commercial Banks Registered In The Indonesia Financial Services Authority With The Camel Ratio - Surya Abbas, Dirvi; Hidaya, Imam (Fakultas Ekonomi dan Bisnis Islam, 2023)
The purpose of this study was to determine the effect of Capital Adequacy Ratio, Non-Performing Finance, Net Profit Margin, Return On Assets, and Finance to Deposit Ratio on Profit Growth in Islamic commercial banks listed in the Financial Services Authority in the 2015- 2018 period. Population This research is all Islamic commercial banks registered with the Financial Services Authority for 2015-2018. The sampling technique used a purposive sampling technique. Based on predetermined criteria, nine companies were obtained. The data used is secondary data obtained from the Financial Services Authority website and the respective Islamic commercial bank websites. The analysis method used is a logistic regression analysis of panel data. The results showed that CAR's capital, management proxied by NPM, and profit proxied by ROA positively affect profit growth, while asset quality proxied by NPF and liquidity proxied by FDR have no impact on profit growth.